ADAPTASI MASYARAKAT DI TUAPEJAT KABUPATEN KEPULAUAN MENTAWAI PROPINSI SUMATERA BARAT - Silvia Devi (Balai Pelestarian Nilai Budaya Sumatera Barat, 2018)
Mentawai is an area consisting of several islands. However, there is one island that was initially notoccupied by the Mentawai people. It was Sipora located exactly in Tuapejat. The island was originallyonly used as a stopover for people who cross the island. However, as the region expands and thensearches for the capital region of the Regency, Sipora Island is chosen as a strategic location for theMentawai people who are on another island. In the past, Mentawai was still part of Pariaman Regency.Then this region became one of the transmigration areas of the population both from West Sumatraitself and from the island of Java. Because of the first entry of transmigration, as well as the existenceof Mentawai people from other islands, they mixed together with a variety of customs and habits.Therefore this paper examines the forms of community adaptation in Tuapejat, Mentawai, West SumatraProvince. This paper uses qualitative approach. The data are collected through interview andobservation. The result of the research shows that there is good adaptation ability among the people inMentawai with the newcomers. The first proces of adaptation is done from the family environment. Theadoption of value is first done in the family before family members interact in the wider environmentsuch as the community. Religious and cultural differences are common in Tuapejat society, especiallyfor Mentawai people. Religious and cultural differences are not a problem among them because theygive priority to mutual respect and value for each difference.